Analysis Of The Effectiveness Of Regional Budget Management In Supporting Infrastructure Development In Deli Serdang Regency - Dina Adelia; Miftha Rizkina; Tia Novira Sucipto (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effectiveness of regional expenditure budget management in supporting infrastructure development in Deli Serdang Regency. Infrastructure development is one of the main priorities of local governments in improving public services, accelerating economic growth, and promoting equitable development. The effectiveness of regional expenditure management is an important indicator of the success of local governments in allocating and realizing budgets in accordance with established plans. This study employs a descriptive quantitative approach using secondary data derived from the Budget Realization Report (LRA) and the Regional Revenue and Expenditure Budget (APBD) of Deli Serdang Regency. The research period focuses on recent fiscal years to examine trends and performance in regional expenditure management. The analytical techniques used include the analysis of regional expenditure effectiveness ratios, infrastructure expenditure growth analysis, and the contribution of capital expenditure to total regional expenditure. The results indicate that, in general, the management of the regional expenditure budget in Deli Serdang Regency has been relatively effective. However, several constraints remain, including the dominance of operational expenditure over capital expenditure and limited realization of infrastructure budgets in certain sectors. This study is expected to contribute to local governments as an evaluation reference and as a basis for formulating more effective budget management policies to support infrastructure development in Deli Serdang Regency.